DEVELOPMENT OF A PROFESSIONAL LEARNING COMMUNITY MODEL INTEGRATED WITH LESSON STUDY TO ENHANCE TEACHERS’ COMPETENCIES IN PROJECT-BASED LEARNING (PjBL) AND TO FOSTER STUDENTS’ INNOVATIVENESS AND INNOVATION CREATION TESSABAN 4 (WAT KHLONG RIAN) SCHOOL - Ninlamost, Manit (Journal of MCU Nakhondhat, 2025)
This research aimed to: 1) Study the needs and directions for developing a model of a Professional Learning Community (PLC) integrated with Lesson Study (LS) to enhance teachers' competence in project-based learning (PjBL) and to foster students' innovativeness and innovation creation; 2) Develop such a model; 3) Implement the model; and 4) evaluate the effectiveness of the model. The target group comprised 29 primary school teachers of Grades 4 - 6 and 326 students at Tessaban 4 (Wat Khlong Rian) School in the academic year 2024. The research instruments included the CREATIV Model and its implementation manual, a teacher competence assessment form, and a student innovation assessment form. Data were analyzed using mean, standard deviation, and content analysis. The findings were as follows: 1) For the needs assessment, the current situation revealed that school administrators recognized the importance of PjBL and teachers had implemented it through the PLC approach; however, limitations remained in teaching experience, instructional techniques, supervision support, and teaching resources. The needs included: establishing mentoring systems, intensive training workshops, regular PLC forums, promoting hands-on learning experiences for students, and improving the learning environment. 2) The developed model, named the CREATIV Model, comprised five components: 2.1) Principles, 2.2) Objectives, 2.3) A seven-step process, 2.4) Measurement and evaluation, and 2.5) Conditions for success. 3) The implementation results showed that 3.1) Teachers demonstrated a high level of competence in designing and implementing PjBL, and 3.2) Students exhibited a high level of innovativeness and innovation creation. 4) The effectiveness evaluation revealed that 4.1) Both teachers and students expressed a high level of satisfaction and 4.2) Positive opinions toward the model and its instructional approach.